Chatting with AI Chatbots Applications to Improve English Communication Skill - Rahman Hakim; Rosmania Rima (Journal of English Language Studies, 2022)
Artificial intelligence allows a person to converse with machines, computers or robots. Chatbots are an application that you can talk to like you would talk to a human. Chatbots can be a tool to practice the language learned anywhere and anytime. In order to improve students' communication skills in English, researchers conducted research on the use of artificial intelligence Chatbots applications in learning English courses in the PKh Department for the 2020/2021 academic year. This study uses a descriptive method to describe the process of learning English with chatbots and to determine student perceptions of the use of these chatbots in improving their communication skills in English. After having conversations with chatbots: ELIZA, ALICE, MITSUKU/KUKI, and ANDY with conversation topics: introductions, feelings/confessions, daily activities, hobbies, lectures, COVID-19 pandemic, etc. The results obtained are the most preferred Chatbots: ANDY, there are POSITIVE meaningful expressions (86%) and no NEGATIVE meanings towards ANDY chatbot. Least favorite chatbots: ELIZA, there are a lot of NEGATIVE (43%) meaningful expressions towards ELIZA chatbot which are bigger than POSITIVE expressions (39%).